2020
DOI: 10.1107/s1600576720010948
|View full text |Cite
|
Sign up to set email alerts
|

Temperature evolution of Fe–27Ga structure: comparison of in situ X-ray and neutron diffraction studies

Abstract: Comparative in situ X-ray and neutron diffraction studies of the phase transitions in a high magnetostriction Fe–27Ga alloy sample have been performed, with heating up to 850°C and subsequent cooling to room temperature. Different structural information (phase content, phase-transition temperatures, unit-cell behaviour) is obtained for the bulk sample and its surface, and this fact is discussed here in terms of the difference between the scattering properties of X-rays and neutrons. In particular, a gallium-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 23 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Phase transitions in the studied alloys are carefully evaluated by real-time neutron diffraction and discussed in this review; Moreover, above-mentioned local phases were reported only by either XRD or TEM methods, which study the surface of the samples. Several papers clearly demonstrated that the bulk and surface structure of Fe–Ga samples is rather different [ 13 , 148 , 149 ]. This is another reason why we exclude discussion on the details of the surface structure of Fe–Ga alloys as all anelastic effects were measured only on a bulk sample.…”
Section: Discussionmentioning
confidence: 99%
“…Phase transitions in the studied alloys are carefully evaluated by real-time neutron diffraction and discussed in this review; Moreover, above-mentioned local phases were reported only by either XRD or TEM methods, which study the surface of the samples. Several papers clearly demonstrated that the bulk and surface structure of Fe–Ga samples is rather different [ 13 , 148 , 149 ]. This is another reason why we exclude discussion on the details of the surface structure of Fe–Ga alloys as all anelastic effects were measured only on a bulk sample.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of neutronograms measured in the in situ mode with continuous heating to ∼ 900 • C and subsequent cooling to room temperature, and diffraction spectra measured with high resolution at a fixed temperature, made it possible to exhaustively characterize the structure and microstructure of alloys in the initial and final to obtain information about structural phase transitions occurring during their heating and cooling. The volumetric nature of the information obtained by neutron diffraction made it possible to exclude the effects associated with the surface layer (gallium evaporation), previously noted by us in the work [7], and local inhomogeneities of the structure [8].…”
Section: Introductionmentioning
confidence: 99%